Perancangan ulang (Re-Layout) tata letak fasilitas menggunakan metode Systematic Layout Planning (SLP) dan Algoritma Blocplan - Laoh, Farid; Lahay, Idham Halid; Darusalam, Jamal (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
UMKM Rm. Mas Joko Seafood Lamongan is a micro, small and medium enterprise or also called a home industry that focuses on selling ready-to-eat food. The problem with this UMKM is the layout that is not properly organized. This can be seen from the location of the unstructured facilities because in the production room it only has a road width of approximately 1 meter and can only be passed by two people, each department always collides in the production process, there are also several departments that are not structured and still have quite a lot of alternating current so that the production process is not optimal. The purpose of this study is to improve the layout of the UMKM Mas Joko Seafood Lamongan production process using the SLP (Systematic Layout Planning) and Blocplan methods so that the results are obtained. In the four proposed layouts, there are savings in the distance between work stations using rectilinear, with a significant difference in distance of 665 m in one production.